Future‐proof: bunkered data centres and the selling of ultra‐secure cloud storage. - Taylor, A.R.E. (Journal of the Royal Anthropological Institute)
Abandoned after the Cold War, nuclear bunkers around the world have found afterlives as ultra‐secure data storage sites for cloud computing providers. The operators of these bunkered data centres capitalize on the spatial, temporal, and material security affordances of their subterranean fortresses, promoting them as 'future‐proof' cloud storage solutions. Taking the concept of 'future‐proofing' as its entry‐point, this essay explores how data centre professionals work with the imaginative properties of the bunker to configure data as an object to be securitized. The essay takes the form of an ethnographic tour through a UK‐based data bunker. During this tour, threatening data futures and fragile data materialities are conjured in order to secure the conditions of possibility for the bunkered data centre's commercial continuity. Future‐proofing, it is argued, provides a conceptual opening onto the entangled imperatives of security and marketing that drive the commercial data storage industry.